2016
DOI: 10.3389/fnagi.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Modulation of Motor Control Biofeedback among the Elderly with High Fall Risk during a Posture Perturbation Task with Augmented Reality

Abstract: The cerebral cortex provides sensorimotor integration and coordination during motor control of daily functional activities. Power spectrum density based on electroencephalography (EEG) has been employed as an approach that allows an investigation of the spatial–temporal characteristics of neuromuscular modulation; however, the biofeedback mechanism associated with cortical activation during motor control remains unclear among elderly individuals. Thirty one community-dwelling elderly participants were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 47 publications
1
42
0
6
Order By: Relevance
“…However, when subjected to the challenging balance conditions, trans-tibial amputees exhibited an increase in alpha power (Petrofsky and Khowailed, 2014). Chang et al (2016) challenged balance control of older adults in high and low fall risk groups by subjecting them to anterior-posterior motion via a Steward Platform. Two conditions were tested with and without a virtual-reality based scenery synchronized with the motion platform.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when subjected to the challenging balance conditions, trans-tibial amputees exhibited an increase in alpha power (Petrofsky and Khowailed, 2014). Chang et al (2016) challenged balance control of older adults in high and low fall risk groups by subjecting them to anterior-posterior motion via a Steward Platform. Two conditions were tested with and without a virtual-reality based scenery synchronized with the motion platform.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also investigated theta band increases in challenging balance tasks in frontal, central, and parietal areas (Hülsdünker et al, 2015, 2016; Chang et al, 2016). Hülsdünker et al (2015) found that theta power over the fronto-central and central-parietal areas correlated with balance performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations